Implementation of Human Resources Management in Efforts to Improve the Performance of Tax Instructors - Yakin, Ipa Hafsiah (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research aims to investigate and analyze the implementation of human resource management (HR) to improve the performance of tax instructors at the Directorate General of Taxes. HR management is essential in creating a work environment that supports employee productivity and motivation, especially in the tax sector. This research uses a qualitative approach with descriptive methods. The research results show that effective implementation of Human Resources Management (HRM) at the Directorate General of Taxes (DJP) has positively impacted the performance of Tax Instructors. Skills development strategies, reward and recognition systems, communication facilitation, and technology integration have formed a supportive and dynamic work environment. Tax Counselors, as the main link between tax regulations and public understanding, can provide more effective counseling services. Apart from that, the policy of balancing work and personal life also contributes to the welfare of Tax Instructors. Thus, the research results confirm that HRM encourages increased individual performance and creates a solid foundation for achieving broader and sustainable tax education goals.